A new genus and two new species of Azeliinae from China (Diptera: Muscidae) - Yang, Kuiwen; Xue, Wanqi; Tong, Yanfeng (Zootaxa, 2022)
A new genus, Chuntiania Xue, gen. nov., including two new species, namely Chuntiania scutiseta Xue, sp. nov. and Chuntiania fuchaooi Xue & Yang, sp. nov., is described from China. A key to the genera of Azeliinae of China is provided, and a morphological comparison diagram of the male cercus of Chuntiania gen. nov. and Potamia Robineau-Desvoidy is added.